2003
DOI: 10.1007/s00192-002-1006-3
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of pelvic organ support in pregnancy

Abstract: Little is known about the anatomic and physiologic changes in the pelvic floor that occur during pregnancy. The purpose of this study was to prospectively document pelvic organ support throughout pregnancy using the standardized system of the International Continence Society, also known as the Pelvic Organ Prolapse Quantification (POPQ) Staging System. Pelvic organ support evaluations were performed in nulliparous pregnant women presenting for routine obstetric care during each trimester. POPQ stage assignment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 0 publications
2
32
1
7
Order By: Relevance
“…A possible explanation is that vaginal delivery is known to cause trauma to the pelvic floor 20 and a macrosomic baby could be even more traumatic resulting in significant damage to the pelvic floor muscles thus increasing the genital hiatus. Vakili et al 21 showed that both a diminished levator ani contraction and a widened genital hiatus correlate with higher rate of prolapse recurrence the early postoperative period.…”
Section: Discussionmentioning
confidence: 97%
“…A possible explanation is that vaginal delivery is known to cause trauma to the pelvic floor 20 and a macrosomic baby could be even more traumatic resulting in significant damage to the pelvic floor muscles thus increasing the genital hiatus. Vakili et al 21 showed that both a diminished levator ani contraction and a widened genital hiatus correlate with higher rate of prolapse recurrence the early postoperative period.…”
Section: Discussionmentioning
confidence: 97%
“…[14][15][16][17][18] A study following nulliparous Chinese women found a peak prevalence of anatomic POP in the third trimester of 35-37%, followed by a significant decline in the first year postpartum, although less in women delivered vaginally compared with women delivered by caesarean. 18 In contrast, a study following British women for up to 5 years postpartum found that vaginal delivery was associated with a persistent worsening in mean POP-Q stage, from 0.61 in the second trimester to a peak of 1.23 at 14 weeks postpartum, then 0.97 at 1 year postpartum and 1.06 at 5 years postpartum.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Studies presenting clinical data addressing these issues are few and their results are conflicting. [14][15][16][17][18] A search on PubMed did not reveal any longitudinal study following the same subjects during pregnancy and onwards throughout the first year postpartum, looking at change in pelvic organ support over time. [14][15][16][17][18] This is a prospective observational study aiming to describe the natural history of pelvic organ support from mid pregnancy to 1 year postpartum using the pelvic organ quantification (POP-Q) system in women having their first child.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of these changes, there may be a reduction in support of the bladder neck and proximal urethra, predisposing pelvic floor (PF) dysfunctions 2,3 , which may become more prevalent as the pregnancy progresses and are associated with the pressure exerted by the fetal head on the bladder 4,5 . O'Boyle et al 6 observed a significant increase in urethral mobility in primigravidae, suggesting that physiological changes occur in the pelvic floor (PF) during pregnancy. However, little is known about the changes that occur in the pattern of electromyographic activity of PFMs during pregnancy, and there are no studies in the literature comparing the pattern of electromyographic activity between the different gestational trimesters of primigravidae.…”
Section: Introductionmentioning
confidence: 99%